Comparison of Early vs. Delayed Anakinra Treatment in Patients With Adult Onset Still's Disease and Effect on Clinical and Laboratory Outcomes - Vitale, Antonio; Cavalli, Giulio; Ruscitti, Piero; Sota, Jurgen; Colafrancesco, Serena; Priori, Roberta; Valesini, Guido; Argolini, Lorenza Maria; Baldissera, Elena; Bartoloni, Elena; Cammelli, Daniele; Canestrari, Giovanni; et al. (Frontiers in Medicine, 2020)
Background: Aim of this study was to search for any difference in the outcome of patients with adult onset Still’s disease (AOSD) treated with anakinra (ANA) in relationship with the delay between disease onset and start of anti-IL (interleukin)-1 treatment and according with the different lines of ANA treatment. Patients and Methods: One hundred and forty-one AOSD patients treated with ANA have been retrospectively assessed. Statistically significant differences (p<0.05) were analyzed in the frequency of ANA efficacy, primary or secondary inefficacy to ANA and rate of resolution of clinical and laboratory AOSD manifestations after 3, 6 and 12 months since ANA treatment according with different lines of treatment and different times between AOSD onset and start of ANA. Results: No significant differences were identified in the efficacy of ANA and frequency of primary or secondary inefficacy for patients starting ANA within 6 months (p=0.19, p=0.14, and p=0.81, respectively) or 12 months (p=0.37, p=0.23, and p=0.81, respectively) since AOSD onset compared with patients starting ANA thereafter; no significant differences were identified in ANA efficacy and primary or secondary inefficacy according with different lines of ANA treatment (p=0.06, p=0.19, and p=0.13, respectively). Patients starting ANA within 6 and 12 months since AOSD onset showed a significantly quicker resumption of erythrocyte sedimentation rate and C-reactive protein than observed among patients undergoing ANA treatment after 6 and 12 months. The number of swollen joints at the 3-month follow-up visit was significantly lower among patients undergoing ANA within 6 months since AOSD onset (p=0.01), while no significance was identified at the 6- and 12-month assessments (p=0.23 and p=0.45, respectively). At the 3- and 6-month visits, the number of swollen joints was significantly higher among patients previously treated with conventional and biological disease modifying anti-rheumatic drugs (DMARDs) compared with those formerly treated only with conventional DMARDs (p<0.017). Conclusions: Clinical and therapeutic outcome are substantially independent of how early ANA treatment is started in AOSD patients. However, a faster efficacy of ANA in controlling systemic inflammation and resolving articular manifestations may be observed in patients benefiting from IL-1 inhibition as soon as after disease onset.